The heist : a novel - Silva, Daniel, 1960- (New York, NY : HarperLuxe, 2014)
Gabriel Allon, art restorer and occasional spy for Israel, must play a dangerous game of high stakes international intrigue as he searches for a stolen masterpiece by Caravaggio.
Keywords: Allon, Gabriel (Fictitious character) -- Fiction; Art thefts -- Fiction; Art restorers -- Fiction; Large type books; Suspense fiction; Spy stories